What Is the Role of AI in Global Health Equity? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Artificial Intelligence (AI) is rapidly transforming the healthcare landscape, offering unprecedented opportunities to address some of the most pressing chal...
Keywords: AI Ethics in Healthcare; Global; Health; Equity; Artificial Intelligence; Deep Learning; Healthcare